miR-137 inhibits proliferation of melanoma cells by targeting PAK2 - Hao, Shuai; Luo, Chonglin; Abukiwan, Alia; Wang, Guangxia; He, Jinjun; Huang, Lingyun; Weber, Claudia; Lv, Na; Xiao, Xueyuan; Eichmüller, Stefan B.; He, Dacheng (Experimental dermatology, 2015)
MicroRNAs (miRNA) are key players in a variety of cancers including malignant melanoma. miR-137 has been reported to be a tumor suppressor in melanoma and several targets have been identified for this miRNA. We previously developed a novel proteomics technology, 35S in vivo/vitro labelling analysis for dynamic proteomics (SiLAD). Because of its high sensitivity in analysing protein expression rates, SiLAD has the potential to unravel miRNA effects on mRNAs coding for proteins with long half-lives or high abundance. Using SiLAD, we discovered that miR-137 significantly downregulated the expression rate of p21-activated kinase 2 (PAK2) in melanoma cells. Bioinformatics analysis predicted PAK2 as a direct target of miR-137, which was confirmed by luciferase reporter assay and Western blot analysis. We found that overexpression of miR-137 inhibited the proliferation of melanoma cells, which could be phenocopied by knockdown of PAK2 using siRNAs. Furthermore, overexpression of PAK2 restored miR-137-mediated suppression of cell proliferation. These findings indicate that miR-137 could inhibit proliferation through targeting PAK2 in melanoma cells.
Gesehen am 29.11.2018